1985
DOI: 10.1111/j.1944-9720.1985.tb00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Schema Theory to Foreign Language Reading

Abstract: In this article, reading is considered to be an interactiveprocess in which the schematic information a readerpossesses for the topic of a given text is as important to adequate comprehension as the information presented on the printed page. When reading in a foreign language, understanding of that language's accompanying culture enables students to approach reading topics from the appropriate cultural perspective. Several classroom activities are described for use before reading, while reading, and after read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Barry and Lazarte (1995) report that providing background knowledge about reading made a difference for the intermediate students of Spanish, but only for relatively simple texts. Melendez and Pritchard (1985) offer suggestions for prereading activities, such as the use of movies, travelogues, visiting speakers, and more. They also suggest ways to activate appropriate schemata, with students forming expectations and making predictions about the content they are to read.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…Barry and Lazarte (1995) report that providing background knowledge about reading made a difference for the intermediate students of Spanish, but only for relatively simple texts. Melendez and Pritchard (1985) offer suggestions for prereading activities, such as the use of movies, travelogues, visiting speakers, and more. They also suggest ways to activate appropriate schemata, with students forming expectations and making predictions about the content they are to read.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…cially for beginning and intermediate L2/FL students (Carrel1 and Eisterhold 1983;Hammadou 1991;Levine and Haus 1985;Lee 1986aLee , 1986b. On the other hand, lack of relevant prior knowledge as well as gaps in cultural background information inhibit or distort comprehension (Melendez 1985). The importance of prior knowledge in the comprehension process has suggested that in both L2/FL and L1 "what is understood depends [more] on the reader rather than on the linguistic difficulty of the text" (Swaffar et al 1991).…”
Section: Fureign Language a N N~w M E R 1999mentioning
confidence: 99%
“…Questions, used to guide discussion of the cornparative advance organizers and stories, are the third component of the sets of lesson materials. Pre-reading questions were written to increase students' consciousness of their own cultural beliefs and establish expectation for learning unfamiliar beliefs (Melendez & Pritchard, 1985). Following are examples of pre-reading questions.…”
Section: Storiesmentioning
confidence: 99%